Ailton Krenak, person-poetry in performance - Silva, Míriam; Dravet, Florence (Revista Brasileira de Estudos da Presença, 2025)
The aim here is to read Krenak’s movement between worlds based on the observation of his performance in the media and institutional spaces, such as his entry into the Brazilian Academy of Letters. Through the essay and the notion of person-poetry, the anthropophagic methodology is used, with the critical and comprehensive reading of his work in relation to other references. A dialogical movement was made when thinking about the person-poetry based on Krenak’s philosophy and about the expression of his philosophy and political action. It is concluded that poetry in Krenak is an ontological condition, life itself that manifests in the body, in words and in political action and allows him to develop his performance.